Dual-head marking performance optimisation via evolutionary solutions - Koh J.; Tiong S.K.; Aris I.B.; Mahmoud S. (2023)
This paper presents a new approach to optimise the performance of a multi-head marking system in terms of its marking speed This processing method named as MMA (Molecular Marking Optimisation algorithm) will adopt the use of Genetic Algorithm. The advantage of the 'self-evolving' nature of the Genetic Algorithm has been considered to discover the most relevant combination of features for each diagnosis considered. The knowledge acquired by the process is interpreted and mapped into vectors, which are kept in the database and used by the system to guide its reasoning process. The representation approach has been implemented via computer program in order to achieve optimised marking performance. Also, the performance of the new operators for evolutionary approaches to the time-based problem has been discussed in the paper. 2005 IEEE.